1984
DOI: 10.1046/j.1468-2982.1984.0404213.x
|View full text |Cite
|
Sign up to set email alerts
|

A Chronobiological Study of Melatonin, Cortisol Growth Hormone and Prolactin Secretion in Cluster Headache

Abstract: The temporal organization of plasma melatonin, cortisol, growth hormone (GH) and prolactin secretion was examined in healthy rested controls and in patients suffering from episodic cluster headache. Eleven patients with typical cluster headache (10 men, 1 female) and 8 male controls were studied over a 24-h period: blood was collected at 2-h intervals during the day and at 1-h intervals at night. Plasma melatonin, cortisol, GH and prolactin levels were determined by radioimmunoassay. Most of the cluster headac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
113
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(126 citation statements)
references
References 14 publications
8
113
0
5
Order By: Relevance
“…Melatonin may be involved in CH attacks. Chazot et al [3] have reported a decrease in melatonin secretion at night and disappearance of melatonin rhythm in patients with CH. Plasma melatonin levels decreased and there was no melatonin rhythm either in non-rapid eye movement sleep, rapid eye movement sleep, or waking during cluster periods.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Melatonin may be involved in CH attacks. Chazot et al [3] have reported a decrease in melatonin secretion at night and disappearance of melatonin rhythm in patients with CH. Plasma melatonin levels decreased and there was no melatonin rhythm either in non-rapid eye movement sleep, rapid eye movement sleep, or waking during cluster periods.…”
Section: Discussionmentioning
confidence: 97%
“…CCH occurs daily without remission periods. CH may be caused by a decrease in nocturnal melatonin levels and a loss of melatonin rhythm [3] . In a small double-blind, placebo-controlled study in 20 patients with CH, melatonin reduced CH frequency compared with the placebo [4] .…”
Section: Introductionmentioning
confidence: 99%
“…У пациентов с эпизодической кластерной головной болью уровень ночной выработки мелатонина снижается во время периода обострения [8,10,28] или может совсем отсутствовать суточная ритмика выработки мела-тонина [9,10]. В ряде исследований у пациентов, страда-ющих кластерной головной болью, во время ремиссии определяется более низкий уровень мелатонина по срав-нению со здоровыми людьми [29,30].…”
Section: кластерная головная больunclassified
“…Примечательно, что в супрахиазматическом ядре гипоталамуса [5,6] определя-ются мелатониновые рецепторы MT1 и MT2, что делает возможным прямое воздействие экзогенного мелатонина на гипоталамус. Во время периода кластеров ночной пик выделения эндогенного мелатонина может снижаться или даже отсутствовать [7][8][9][10][11], при этом экзогенное вве-дение мелатонина может восстановить этот ритм.…”
Section: Introductionunclassified
“…Of relevance, is that both melatonin and serotonin seem to be involved in hypersensitivity and pain conductance in mice [157] and that melatonin treatment alleviates pain in IBS [158] and (vide supra [112]) acting along the brain-gut axis [159]. Melatonin has also been implicated in cluster headaches, lower nocturnal secretion (advanced phased) melatonin, as reported by Chazot et al, [160] but cause-effect inferences must be guarded ones. However, a logical explanation could be sleep management given that melatonin is sometimes referred to as the 'dark' or 'sleep' hormone.…”
Section: Gastrointestinal Melatonin Secretion and Interaction With Sementioning
confidence: 99%